A Study to Assess the Behavioural and Psychological Symptoms in Patients with Dementia - Singh, Dr. Manjit; Kaur, Dr. Manmeet; Garg, Dr. P. D.; Bala, Dr. Neeru (International Journal of Innovative Research in Medical Science, 2019)
Introduction: With the aging population, the prevalence of dementia is rising. The aim of the study was to assess the frequency of Behavioural and Psychological symptoms (BPSD) in patients with dementia. Materials and Methods: A semi-structured proforma was used to gather sociodemographic details including age, gender, educational status, economic status, living conditions, family and personal history of any psychiatric illness. Mini Mental Status Examination was administered to record the level of cognitive impairment. Neuropsychiatric Inventory (NPI) was used to assess the presence of behavioral and psychological symptoms of dementia (BPSD) in patients with dementia. Findings: Out of 54 patients, 53.7% were females and 46.3% were males. 61.12% were above 65 years of age. Most of them 51.85% were illiterate. 66.67% belong to rural background. 59.25% came from nuclear families. MMSE score distribution showed that 51.85% belong to mild dementia group. Mean MMSE score was 16.12+/-4.778 SD. On Neuropsychiatric Inventory (NPI), most common symptoms were apathy (70. 37%), agitation (64.8%), sleep disturbances (59.25%) followed by other symptoms. Mean item score was 27.84+/-17.58 SD. Mean distress score was 17.72+/-8.99 SD. Conclusion: BPSD are universally present in patients with dementia and cause significant caregiver distress.